Hybrid nanofluid stagnation point flow past a slip shrinking Riga plate - Wahid, Nur Syahirah; Md Arifin, Norihan; Khashi'ie, Najiyah Safwa; Pop, Ioan; Bachok, Norfifah; Hafidzuddin, Mohd Ezad Hafidz (Elsevier, 2022)
Magnetic nanofluids cover many of uses since their characteristics are externally controllable, and their physical properties may vary with the nanoparticle volume fraction and magnetic field strength. Hybrid nanofluid also has been commercialized as the advancement of traditional nanofluid. The preliminary research on hybrid magnetic nanofluids inspired the present study to discover the stagnation-point flow of hybrid magnetite-cobalt ferrite/water nanofluid towards a shrinking Riga plate with the presence of velocity slip. The complex governing model of the flow is simplified by implementing the similarity transformation. A well-established numerical package, namely bvp4c in MATLAB, is used for numerical calculation as well as stability analysis. Two solutions are found due to the opposing flow from the shrinking Riga plate. From the stability analysis, the first solution which fulfills the boundary condition is the physically stable solution. The rising values of electromagnetohydrodynamic (EMHD) parameter and cobalt ferrite concentration augment the skin friction coefficient. Specifically, the critical point is lessened by 3% when the EMHD parameter is augmented from 0.3 to 0.5 and 0.5 to 0.7, which concludes that a suitably higher EMHD parameter could prevent the separation of the boundary layer. The heat transfer progress is actively performed with the enhancement of EMHD and velocity slip parameters which conclusively shows the suitability of these parameters in developing the cooling heat transfer fluid.